Genomic Characterization of Listeria monocytogenes Isolated From Ready-to-Eat Meat and Meat Processing Environments in Poland - Kurpas, Monika; Osek, Jacek; Moura, Alexandra; Leclercq, Alexandre; Lecuit, Marc; Wieczorek, Kinga (Frontiers in Microbiology, 2020)
Listeria monocytogenes is one of the major foodborne pathogens. Isolates of PCR-serogroups IIb (n = 17) and IVb (n = 31) recovered from food (n = 33) and food processing environment (n = 15) in Poland were characterized using whole genome sequencing. Most isolates belonged to Multi-Locus Sequence Type (MLST) ST2 (31.3%) and ST5 (22.9%). Core genome MLST (cgMLST) analysis classified isolates into 7 sublineages (SL) and 25 different cgMLST types (CT). Consistent with the MLST results, most sublineages were SL2 and SL5. Eleven isolates harboured aacA4 encoding resistance to aminoglycosides, 3 isolates harboured emrC (n = 3) and one brcABC (n = 1) encoding tolerance to benzalkonium chloride. Isolates belonging to SL5 CT2323 carried a so far unreported inlB allele with a deletion of 141 nucleotides encoding the β-repeat sheet and partially the GW1 domain of InlB. Comparison with publicly available genome sequences from L. monocytogenes isolated from human listeriosis cases in Poland from 2004 to 2013 revealed 5 common CTs, suggesting a possible epidemiological link with these strains. The present study contributes to characterize the diversity of L. monocytogenes in ready-to-eat (RTE) meat and meat processing environments in Poland and unravels previously unnoticed links with clinical cases in Europe.